Body-image and bullying experience in adolescents - Bagdonas, Albinas; Padarauskaitė, Indrė (Psichologija, 2012)
Bullying is a very common behaviour among adolescents, which has an effect on a child’s psychological well-being. Research has shown that there are many different ways how bullying may affect children, and usually the children that experience bullying report a lower self-esteem and body dissatisfaction. The purpose of this study was to find a relationship among bullying, gender, body mass index and self-image. The study involved 101 participants (age 15). All the participants were given a questionnaire containing two parts: one part consisted of questions about bullying experience, and appearance scales from Multidimensional Body-Self Relations Questionnaire were used in the second part. The results have shown that almost half of the participants are actively involved in bullying. Most of them have reported being bullies themselves. There were twice as many girls who were victims of bullying as compared with boys. The children that are victims of bullying have less friends than those who are not involved in bullying at all. Our findings have also shown how children perceive their appearance. Girls place more importance than boys on how they look. Girls also reported dissatisfaction with their weight more often than boys did. We also found a link between the body mass index and appearance evaluation and between the body mass index and bullying. Those whose body mass index is higher are more inclined to watch their weight, diet or in any other way avoid weight gain. Those whose body mass index is higher also more often reported to be victims of bullying than those with a lower body mass index. A more detailed analysis has indicated that those who are victims of bullying more often feel unhappy about their physical appearance and are more oriented to their physical appearance than those who are not involved in bullying. The children that have less or no friends in their form also tend to feel less satisfied with their appearance. Those who are bullies themselves place least importance on how they look.
Keywords: bullying; teenager; body mass index; body image; satisfaction with body